An investigation on benefits and future expectation of Industrialised Building System (IBS) implementation in construction practices - Ismail, Hassan; Akasah, Zainal Abidin; Nagapan, Sasitharan; Khamis, Azme (RMP Publications, 2018)
Industrialised Building System (IBS) is well known in many developing countries due to the benefits that can be derived from its applications in construction projects. However, the low percentage of IBS usage may be due to lack of awareness and knowledge about IBS among many professionals. There may be factors that contribute to a lack of interest from the client towards IBS. The aim of this study is to improve the application of IBS particularly in private construction projects in Malaysia by determining the benefits and expectation on application of IBS in private construction projects. This study adopts a quantitative method using questionnaires that were sent to 35 construction firms as a sampling frame. Finally, the finding of this study hopefully could assist professional parties in construction industry in providing a better ground knowledge for improving decisions making to achieve the success of IBS construction projects implementation and also this study will achieved the project objectives in terms of predetermined objectives that are mostly within the time, specified budget and standard quality